Twilight - Morgan, Melissa J. (New York : Grosset & Dunlap, 2009)
As sixteen-year-old Cassie's summer at Camp Ohana draws to a close, her romance with Micah blossoms, kindling the wrath of bunkmate Danica, while her terror of resuming her professional surfing career continues unabated.
Keywords: Camps -- Juvenile fiction; Camp counselors -- Juvenile fiction; Surfing -- Juvenile fiction; Self-confidence -- Juvenile fiction; Interpersonal relations -- Juvenile fiction; Camps -- Fiction; Camp counselors -- Fiction; Surfing -- Fiction; Self-confidence -- Fiction; Interpersonal relations -- Fiction; Hawaii -- Juvenile fiction; Hawaii -- Fiction